Empathy Design Thinking: cultivating creative minds in primary education - Liu, Wei; Huang, Ruonan; Wang, Jun; Chen, Yinghe; Ohashi, Takumi; Li, Bowen; Liu, Yiyang; Qiu, Dan; Yu, Ruilu; Zhang, Jingjing; Al Mahmud, Abdullah; Leifer, Larry (Frontiers in Education, 2024)
This research explores the application of an Empathy Design Thinking (EDT) curriculum within primary education, guided by the principles of Experience, Empathy, Exploration, and Evaluation, to examine its effect on fostering student creativity in a Chinese context. The curriculum was redesigned into a streamlined, modular format for ease of integration into existing educational frameworks. Findings demonstrate a positive impact on students' creative thinking abilities, particularly in enhancing fluency and flexibility, with notable mentions of empathy's vital role in the educational process. This study aligns with global educational trends emphasizing the need for empathetic and comprehensive learning experiences, offering insights into the potential of EDT to enrich creative education for primary students, educators, curriculum developers, and policymakers.